Pseudo periodic Higgs inflation - Márián, István Gábor; Defenu, Nicolò (Arxiv, 2017)
There is a strong interest in finding a link between Higgs scalar fields and inflationary physics. A good Higgs-inflation potential should have a form as simple as possible, provide agreement with observations and be used, once its parameters are determined from experimental data, to make predictions. In literature the presence of one or possibly more minima of several class of potentials has been discussed: here we focus on a potential having infintely many non-degenerate minima, with a tunable energy difference between them. Such potential has the advantage of having a unique ground-state, but at the same time with other minima that can excited. The potential having such property, that we term pseudo periodic potential, reads $V(\phi) = m^2 \phi^2/2 + u [1-\cos(\beta \phi)]$ is a combination of quadratic monomial and periodic terms, known as massive sine-Gordon model. We show that it provides an excellent agreement with observations on the fluctuations of cosmic microwave background radiation, contains two adjustable parameters (the ratio $u/m^2$ and the frequency $\beta$) and can be considered as a convenient reparametrization of $\phi^{2n}$ models. We discuss the applicability of the model for inflationary cosmology and for Higgs-inflation. Finally, motivated by the need of extract properties independent for the specific form of the potential, we perform a renormalization group (RG) running in the post-inflation period and we investigate the consequences of the RG running on convexity for the considered pseudo periodic potential. The implications of the obtained results for a more systematic use of RG are finally discussed.
Identifizierung der Ressource nach: last revised 15 Jul 2019
Gesehen am 13.10.2020